The role of biogeographical barriers and bridges in determining divergent lineages in Ficus (Moraceae). (6th July 2018) - Pederneiras, Leandro Cardoso; Gaglioti, André Luiz; Romaniuc-Neto, Sergio; Mansano, Vidal de Freitas
Abstract: Studies that place the origin of the stem node of Ficus in Gondwana or Eurasia at c. 136–134 Mya are not congruent with the estimated origin of Moraceae in the Late Cretaceous. To elucidate these origins, molecular analyses were performed using three calibration points in BEAST with 268 terminal taxa based on ITS, ETS, G3 pdh, ncp GS and GBSSI sequences. S-DIVA, DEC and S-DEC were used to estimate ancestral areas. The arrangement of staminate flowers within the syconium supports the current phylogenetic framework of Ficus . Our results suggest that the stem lineage of Ficus originated at the beginning of the Cenozoic among the boreotropical flora around the Tethys Seaway, and that the crown lineage radiated during the Eocene. Ficus reached the Americas via two routes: from Europe to North America in the Early Eocene, giving rise to F. section Pharmacosycea, and from Africa to South America in the Late Eocene via the trans-Atlantic route, giving rise to F. section Americanae . East Asia appears to have played an important role in the evolution of species with staminate flowers grouped in the ostiole, here named the Androstiole clade. In the Oligocene, these species probably migrated to South-East Asia, reuniting with lineages of F. subgenus Spherosuke .